PEMBIMBINGAN PEMUDA PENGGUNAAN MEDIA SOSIAL AGAR TETAP MEMILIKI KOMUNITAS SEBAGAI MEDIA INTERAKSI VERBAL - Victor Abraham; Yanto Paulus Hermanto (Jurnal PKM Setiadharma, 2023)
Social media has become an important part of the daily lives of youth in Indonesia. However, the influence of social media can be unhealthy if used excessively or in the wrong way. Community can be a solution for youth who experience negative social media influences. This article discusses the role of the community in helping youth overcome the negative effects of social media influence and encourage positive development within youth in Indonesia. This journal uses qualitative research methods with a case study approach or participant observation. Through writing this journal, the authors can draw conclusions that the community can play a very crucial role in helping to increase public understanding and awareness of the benefits of technology. The results obtained can also provide insight that the community can play a crucial role in helping people optimize the use of technology and social media. So this research contributes not only to reminding social media users out there to be wise about the use of social media, but this research also reminds community activists out there who really understand the potential of social media in this era to teach and guide in any form to the public. Indonesia, so that the Indonesian state can progress rapidly as is the progress in existing technology.